Building adaptive capacity of smallholder agriculture to climate change: evidence synthesis on learning outcomes - Silici, Laura; Rowe, Andy; Suppiramaniam, Nanthikesan; Knox, Jerry W. (IOP Publishing, 2021)
Increasing climate uncertainty coupled with more frequent extreme events poses a serious threat to the sustainability of smallholder communities dependent on agriculture for their livelihoods. Whilst there is extensive literature on adaptation options, there is a pressing need to understand what interventions have been successful in building smallholder’s adaptive capacity, and how these have been transferred (nationally and internationally)through learning outcomes. The aim of this rapid evidence assessment was to assess the extent to which learning outcomes have supported initiatives to mainstream adaptation, focussing on three key areas, (i)scaling up climate sensitive adaptive interventions, (ii)the role of knowledge management to promote effective adaptive solutions, and (iii) human-ecosystem interactions in climate change adaptation. A protocol for the review was defined, from which 806 sources of evidence were retrieved. After screening for relevance using inclusion criteria, 91 were selected and the salient evidence extracted and synthesised. Access to knowledge remains one of the most important determinants of smallholders’ decisions to respond to climate risk and a critical element in building adaptive capacity. The way knowledge is generated and exchanged is also directly relevant to securing effective scaling-up pathways. Learning platforms through participatory action research, farmer field schools and community-based initiatives were found to be particularly effective. However, knowledge based on local practices alone may be insufficient to prompt transformative action. Bridging local and external knowledge is critical because it widens the smallholders’ knowledge base and encourages ‘proactive’ adaptation alongside more typical ‘reactive’ strategies. The contribution of evidence reviews to provide new insights to inform decision-making and investment in international development and the implications for advocating climate-sensitive policies at national and global levels are discussed.
Keywords: agriculture; development; knowledge management; scaling up; nexus